Unmanned aerial vehicles. Perspectives. Management. Power supply: Multi-authored monograph - Holovenskiy, V. V.; Головенський, В. В.; Shmelova, T. F.; Шмельова, Т. Ф.; Shmelov, Yu. M.; Шмельов, Ю. М.; ORCID: http://orcid.org/0000-0002-3942-2003; Tymochko, O. I.; Boiko, S. M.; Khebda, A. S.; Chyzhova, L. I.; Чижова, Л. І.; et al. (Warsaw, 2019. - 100 p., 2019)
У монографії аналізуються можливі варіанти енергопостачання та управління безпілотними літальними апаратами. Також розглядається питання прийняття рішення оператором безпілотного літального апарату при управлінні у надзвичайних ситуаціях. Рекомендується для фахівців, аспірантів і студентів за спеціальностями 141 - «Електроенергетика, електротехніка та електромеханіка», 173 - «Авіоніка» та інших суміжних спеціальностей.

The monograph analyzes the possible options for energy supply and control of unmanned aerial vehicles. Also, the issue of decision-making by the operator of an unmanned aerial vehicle in the management of emergencies is considered. Recommended for specialists, postgraduate and students in the field of 141 – "Electric power, electrical engineering and electromechanics", 173 – "Avionics" and other related specialties.

В монографии анализируются возможные варианты энергоснабжения и управления беспилотными летательными аппаратами. Также рассматривается вопрос принятия решения оператором беспилотного летательного аппарата при управлении в чрезвычайных ситуациях. Рекомендуется для специалистов, аспирантов и студентов по специальностям 141 - «Электроэнергетика, электротехника и электромеханика», 173 - «Авионика» и другим смежным специальностям.
Multi-authored monograph
Unmanned aerial vehicles. Perspectives. Management. Power supply : Multi-authored monograph / V. V. Holovenskiy, T. F. Shmelova,Y. M. Shmelev and oth.; Science Editor DSc. (Engineering), T. F. Shmelova. – Warsaw, 2019. – 100 p. - ISBN 978-83-66216-10-5.
Keywords: Монографії. Monographs. Монографии; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; беспилотные летательные аппараты; энегроснабжение; управление в чрезвычайных ситуациях; авионика; электротехника; электромеханика